2016
DOI: 10.1038/mi.2015.128
|View full text |Cite
|
Sign up to set email alerts
|

Lung epithelium and myeloid cells cooperate to clear acute pneumococcal infection

Abstract: The Gram-positive bacterium Streptococcus pneumoniae causes life-threatening infections, especially among immunocompromised patients. The host's immune system senses S. pneumoniae via different families of pattern recognition receptors, in particular the Toll-like receptor (TLR) family that promotes immune cell activation. Yet, while single TLRs are dispensable for initiating inflammatory responses against S. pneumoniae, the central TLR adapter protein myeloid differentiation factor 88 (MyD88) is of vital impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 62 publications
(102 reference statements)
1
25
0
Order By: Relevance
“…Moreover, release of IL-12p70 and IFN-␥, which are also involved in phagocyte recruitment and potentiation of phagocytic killing (38)(39)(40)(41), was almost completely abrogated in the triple KO mice. Thus, the mechanisms underlying the hypersusceptibility of TLR7/9/13 triple KO mice to pneumonia are similar to those previously identified in MyD88-deficient mice, in which chemokine production and neutrophil recruitment to the lung were severely impaired (11). In the present study, the defects in chemokine and cytokine production observed in vivo were mirrored in vitro by impaired release of these mediators by AM and other resident macrophages after stimulation with pneumococci.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, release of IL-12p70 and IFN-␥, which are also involved in phagocyte recruitment and potentiation of phagocytic killing (38)(39)(40)(41), was almost completely abrogated in the triple KO mice. Thus, the mechanisms underlying the hypersusceptibility of TLR7/9/13 triple KO mice to pneumonia are similar to those previously identified in MyD88-deficient mice, in which chemokine production and neutrophil recruitment to the lung were severely impaired (11). In the present study, the defects in chemokine and cytokine production observed in vivo were mirrored in vitro by impaired release of these mediators by AM and other resident macrophages after stimulation with pneumococci.…”
Section: Discussionsupporting
confidence: 87%
“…To investigate the importance of MyD88 in DCs, we next crossed ItgaxCre mice (Caton et al, 2007) or pDCre mice (Puttur et al, 2013) with MyD88 OFF mice. The mice generated from these crossings, here termed DC-MyD88 ON and pDC-MyD88 ON , reactivate Myd88 gene expression in CD11c + cells or in Siglec-H + cells, respectively, and have been carefully characterized in our previous work (Arnold-Schrauf et al, 2014;Berod et al, 2014;Dudek et al, 2016). Reactivation of MyD88 in CD11c + cells (DC-MyD88 ON ) significantly improved clearance of MCMV compared to mice that reactivated MyD88 only in a representative fraction of pDCs (pDC-MyD88 ON ) or mice that lacked MyD88 in all cells (MyD88 OFF ) ( Figures 1H and 1I).…”
Section: (Legend Continued On Next Page)mentioning
confidence: 99%
“…In order to study the specific role of MyD88 in the epithelium as well as DCs and macrophages, we used the MyD ON mouse model for Cre-mediated activation of functional MyD88. We and others have shown that this model allows the precise study of direct consequences of cell type-specific TLR-mediated signaling on the immune response [27,30,[36][37][38][39]. This gain-offunction model enabled us, as demonstrated previously, to restrict functional MyD88 signaling to the intestinal epithelium or CD11c + MNPs, encompassing both DCs and macrophages in intestinal tissues, while all other cells and tissues of the body remain deficient for MyD88 [30].…”
Section: Discussionmentioning
confidence: 66%